2007
DOI: 10.1093/epirev/mxm004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Epidemiology of Obesity

Abstract: Obesity has become a global epidemic and contributes to the increasing burden of type 2 diabetes, cardiovascular disease, stroke, some types of cancer, and premature death worldwide. Obesity is highly heritable and arises from the interactions of multiple genes, environmental factors, and behavior. In this paper, the authors reviewed recent developments in genetic epidemiologic research, focusing particularly on several promising genomic regions and obesity-related genes. Gene-gene and gene-environment interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
203
4
20

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 255 publications
(231 citation statements)
references
References 164 publications
4
203
4
20
Order By: Relevance
“…The effects of the candidate gene markers could be validly evaluated after controlling for environmental factors (e.g. physical activity, diet, smoking) and ethnicity (6,55). Finally, the answer to the question of whether or not the findings from this study can be generalized to Croatian population remains uncertain because analysis was performed in a rather small group.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The effects of the candidate gene markers could be validly evaluated after controlling for environmental factors (e.g. physical activity, diet, smoking) and ethnicity (6,55). Finally, the answer to the question of whether or not the findings from this study can be generalized to Croatian population remains uncertain because analysis was performed in a rather small group.…”
Section: Discussionmentioning
confidence: 94%
“…The increasing prevalence of obesity in the European Union and the USA is a major health concern, and it is also becoming worrying in Croatia (4) In Croatia, the prevalence of overweight, obesity and central obesity is estimated to be 38.11%, 20.34% and 43.52%, respectively (5). The genetics of obesity is complex and involves interactions between genes, gene and environment, and gene and nutrition and behavioral factors (6). Genome-wide association studies (GWAS) have identified numerous obesityrelated loci but precise identification of correlation between DNA sequence variation in specific gene and obesity phenotypes has been difficult (7).…”
Section: Introductionmentioning
confidence: 99%
“…6 At similar BMI levels, however, the amount of abdominal fat and associated health risk can differ significantly. A more sensitive measure is waist circumference, which gives information about the central fat distribution and is used to define abdominal obesity.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 For waist, the heritability estimates range from 40 to 80%. 6 The 2005 update of the human obesity gene map reported 426 associations between candidate genes and obesity phenotypes. 8 Despite the long list of positive findings, meta-analyses showed sufficient evidence for an association with BMI or obesity for five genes only (PPARY2, FTO, MC4R, TNFa, PCSK1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation